2020
DOI: 10.31635/ccschem.019.201900043
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemistry of an Interlocked Poly[2]catenane: From Single Molecule to Bulk Gel

Abstract: Citation denotes calendar and volume year of first online publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 8 publications
0
38
0
Order By: Relevance
“…In addition to classic ensemble measurements, we used atomic force microscopy (AFM)-based single-molecule force spectroscopy (SMFS) to measure the strength of binding between the three different RBDs and ACE2 on a living cell directly ( Alsteens et al, 2017a ; Hinterdorfer and Dufrêne, 2006 ). AFM-SMFS is a powerful single-molecule nanotechnology that can be used like optical and magnetic tweezers to manipulate a single molecule or several molecules mechanically ( Jobst et al, 2015 ; Walder et al, 2017 ; Alonso-Caballero et al, 2021 ; Löf et al, 2019 ; Huang et al, 2019 ; Zhang et al, 2019 ; Xing et al, 2020 ). It has been widely used to study protein mechanics and protein–protein interactions, including the interaction between the spike proteins of viruses and living cells ( Kim et al, 2010 ; Cuellar-Camacho et al, 2020 ; Yang et al, 2020 ; Sieben et al, 2012 ; Alsteens et al, 2017b ; Yu et al, 2019 ; Ma et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to classic ensemble measurements, we used atomic force microscopy (AFM)-based single-molecule force spectroscopy (SMFS) to measure the strength of binding between the three different RBDs and ACE2 on a living cell directly ( Alsteens et al, 2017a ; Hinterdorfer and Dufrêne, 2006 ). AFM-SMFS is a powerful single-molecule nanotechnology that can be used like optical and magnetic tweezers to manipulate a single molecule or several molecules mechanically ( Jobst et al, 2015 ; Walder et al, 2017 ; Alonso-Caballero et al, 2021 ; Löf et al, 2019 ; Huang et al, 2019 ; Zhang et al, 2019 ; Xing et al, 2020 ). It has been widely used to study protein mechanics and protein–protein interactions, including the interaction between the spike proteins of viruses and living cells ( Kim et al, 2010 ; Cuellar-Camacho et al, 2020 ; Yang et al, 2020 ; Sieben et al, 2012 ; Alsteens et al, 2017b ; Yu et al, 2019 ; Ma et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The theoretical calculation also confirmed that there were evident non-covalent interactions between the benzodithiazole moiety and the adjacent phenyl ring (Figure S12). 52,53 Since temperature change may influence the molecular motion 54,55 and thus change the molecular conformation as well as the microenvironment of the hydrogen atoms, variable-temperature 1 H NMR experiment was thus implemented to monitor the intramolecular hydrogen bonding change of TPABSM with temperature. As shown in Figure S13, with the temperature increasing, the chemical shift of the H atom that participates in the hydrogen bonding formation (Ha) slightly shift to the higher magnetic field.…”
Section: Resultsmentioning
confidence: 99%
“…[ 26–39 ] Synthetic oligomers and polymers have also been investigated by SMFS, which has helped us in the understanding of their nanomechanical properties. [ 40–43 ] Many researches have been done to study the nanomechanical properties of type II helices. [ 44–46 ] However, due to the limitation of detection method and dynamic nature of the structure, it is quite challenging to investigate nanomechanical properties of individual type III supramolecular helices.…”
Section: Methodsmentioning
confidence: 99%